2017
DOI: 10.1186/s13013-017-0128-9
|View full text |Cite
|
Sign up to set email alerts
|

3D correction of AIS in braces designed using CAD/CAM and FEM: a randomized controlled trial

Abstract: BackgroundRecent studies showed that finite element model (FEM) combined to CAD/CAM improves the design of braces for the conservative treatment of adolescent idiopathic scoliosis (AIS), using 2D measurements from in-brace radiographs. We aim to assess the immediate effectiveness on curve correction in all three planes of braces designed using CAD/CAM and numerical simulation compared to braces designed with CAD/CAM only.MethodsSRS standardized criteria for bracing were followed to recruit 48 AIS patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 37 publications
(45 reference statements)
1
38
0
Order By: Relevance
“…Although no significant difference in Cobb angle correction was obtained in group 2 [30], in group 3, the CAD-FEM brace resulted in significantly better in-brace curve correction than that of the conventional brace [53] (Table 4). In a study of Cobetto et al [55],…”
Section: Coronal Plane: Cobb Angle and Coronal Balancementioning
confidence: 94%
See 4 more Smart Citations
“…Although no significant difference in Cobb angle correction was obtained in group 2 [30], in group 3, the CAD-FEM brace resulted in significantly better in-brace curve correction than that of the conventional brace [53] (Table 4). In a study of Cobetto et al [55],…”
Section: Coronal Plane: Cobb Angle and Coronal Balancementioning
confidence: 94%
“…The correlation between brace-manufacturing methods and scoliosis treatment outcomes is controversial. Some studies have reported approximately the same Cobb angle correction between conventional versus CAD-CAM [28,30,54] and between conventional versus CAD-FEM methods [46,51], whereas other studies have shown that the Cobb angle was better corrected by CAD-FEM methods than by CAD-CAM or conventional methods [53,55]. Despite the controversial results in comparing the efficiency of brace-manufacturing methods, to the best of our knowledge, no study has yet carefully reviewed the effect of these methods on scoliosis parameters, such as spinal curve in coronal, sagittal, and transverse planes, and the patient's comfort.…”
Section: Cad-fem (Simulation Methods)mentioning
confidence: 99%
See 3 more Smart Citations